Business data networks and telecommunications - Panko, R. R. (Upper Saddle River, NJ : Pearson Education, 2009)
For undergraduate and graduate business data communications and networking courses. Panko teaches students about the technologies that are being used in the marketplace.
An Introduction to Networking -- Network Standards -- Physical Layer Propagation -- Ethernet LANs -- Wireless LANs -- Telecommunications -- Wide Area Networks (WANs) -- TCP/IP Internetworking -- Hands on: Packet Capture and Analysis with WinDump and TCPDump -- Security -- Network Management -- Networking Applications.
Includes index.
1
Keywords: Networks and Telecommunication; Business enterprises -- Computer networks -- Study guides; Computer networks -- Management -- Study guides; Data transmission systems -- Study guides